Physiology. An overview. Medical course and review of step 1 - Kibble, Jonathan D. (McGraw-Hill's AccessMedicina., 2023)
The aim of this textbook is to help medical students learn and review physiology efficiently. The text offers a comprehensive but concise discussion of major topics in medical physiology and includes a number of design features designed to make the text user-friendly.